A Preliminary Study on the Geoscientific Significance of the Core from Cangzhou Scientific Drilling Hole - Ning Di; Guo Haipeng; Zhu Juyan; Wang Guijie; Wang Haigang; Liu Rui (E3S Web of Conferences, 2025)
The Cangzhou area is one of the regions in China most severely affected by groundwater over- exploitation and land subsidence. To further elucidate the deep geological structure of this area and facilitate dynamic monitoring of key strata compression, the Cangzhou scientific drilling project has undergone a comprehensive range of operations, including drilling, full-hole coring, geological logging, and spectral scanning. A thorough analysis of the core samples indicates that the Cangzhou scientific drilling hole reaches a depth of 1501.69 m, penetrating the Dongying Formation of the Paleogene. The encountered strata are: the Quaternary Holocene Series, the Upper Pleistocene Series, the Middle Pleistocene Series and the Lower Pleistocene Series, and the Neogene Minghuazhen Formation and the Guantao Formation, from top to bottom. At a depth of 1489.60 m, the top boundary of the Dongying Formation is identified at the location of the Cangzhou scientific drilling hole. The main mineral components of the cores are montmorillonite, kaolinite, and gypsum, with 93.10% of the cores containing more than 50% montmorillonite. This data provides substantial support for elucidating the causal mechanisms of land subsidence in the Cangzhou area.